AmniVis – A System for Qualitative Exploration of Near‐Wall Hemodynamics in Cerebral Aneurysms. (1st July 2013) - Neugebauer, M.; Lawonn, K.; Beuing, O.; Berg, P.; Janiga, G.; Preim, B.
Abstract: The qualitative exploration of near‐wall hemodynamics in cerebral aneurysms provides important insights for risk assessment. For instance, a direct relation between complex flow patterns and aneurysm formation could be observed. Due to the high complexity of the underlying time‐dependent flow data, the exploration is challenging, in particular for medical researchers not familiar with such data. We present the AmniVis‐Explorer, a system that is designed for the preparation of a qualitative medical study. The provided features were developed in close collaboration with medical researchers involved in the study. This comprises methods for a purposeful selection of surface regions of interest and a novel approach to provide a 2D overview of flow patterns that are represented by streamlines at these regions. Furthermore, we present a specialized interface that supports binary classification of patterns and temporal exploration as well as methods for selection, highlighting and automatic 3D navigation to particular patterns. Based on eight representative datasets, we conducted informal interviews with two bord‐certified radiologists and a flow expert to evaluate the system. It was confirmed that the AmniVis‐Explorer allows for an easy selection, qualitative exploration and classification of near‐wall flow patterns that are represented by streamlines.